Kajian Kualitas Standar Akuntansi Keuangan Bagi Entitas Mikro, Kecil dan Menengah - Rahmawati, Mia Ika; Susanti, Susanti (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 2 (2018)DO - 10.24843/JIAB.2018.v13.i02.p02, 2018)
The preparation of accurate and standard financial statements will help Micro, Small and Medium Enterprises (MSMEs) in their efforts to develop their businesses and access funding to financial institutions (banks). The presence of Financial Accounting Standards for Micro, Small and Medium Enterprises (MSMEs) is expected to help MSMEs in Indonesia in preparing financial reports that help MSMEs be more independent, strong and advanced. This study focused on the level of understanding and knowledge of SMEs on the existence of financial statements prepared under the applicable financial accounting standards. Data collection methods through in-depth interviews. The results showed that all informants did not understand and did not have knowledge about the issuance of SAK EMKM which became the basis of MSMEs in making financial statements. So the need for socialization, training and workshops to help MSME players have knowledge, understand and apply SAK EMKM in their financial statements. Keywords: SAK EMKM, Perception, Behavior, SMEs